2018
DOI: 10.11594/jtls.08.01.12
|View full text |Cite
|
Sign up to set email alerts
|

Tetracera scandens as a Medicinal Plant: Secretory Structures, Histochemistry, and Antibacterial Activity

Abstract: Tetrascera scandens, a member of Dilleniaceae, is used for traditional medicine; the stem is utilized by the Anak Dalam tribe of Jambi Province, Sumatera island, Indonesia, to treat diarrhea symptoms. The aims of this study were to identify the secretory structures, histochemical aspects, and the antibacterial potency of T. scandens stem. Histological study of the secretory structures of T. scandens stem was carried out. The species has idioblast cells and trichomes as its secretory structures. Histochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…Tetracera scandens is a Southeast Asian medicinal plant with several indications, including diabetes mellitus, hepatitis, rheumatism, urinary illnesses, hypertension and diarrhea [16]. Muliyah et al have demonstrated the antibacterial potential of the methanol extract of T. scandens stem as a proposed mechanism of the antidiarrheal activity of the plant [17]. Moreover, an in vivo study has been conducted to investigate the hepatoprotective and the antioxidant potential of the ethanol extract of T. scandens leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Tetracera scandens is a Southeast Asian medicinal plant with several indications, including diabetes mellitus, hepatitis, rheumatism, urinary illnesses, hypertension and diarrhea [16]. Muliyah et al have demonstrated the antibacterial potential of the methanol extract of T. scandens stem as a proposed mechanism of the antidiarrheal activity of the plant [17]. Moreover, an in vivo study has been conducted to investigate the hepatoprotective and the antioxidant potential of the ethanol extract of T. scandens leaves.…”
Section: Introductionmentioning
confidence: 99%
“…A woody climber, Tetracera scandens was in full bloom when we found it at the roadside of the main road to the Lasitae PF (Figure 11a). This plant grows widely in India, China, Indonesia, Myanmar, Philippines, Thailand, Malaysia, and Vietnam (Thanh et al, 2015;Muliyah et al, 2017). The trunk can be used as a source of drinkable water if it is unavailable in the forest.…”
Section: Discussionmentioning
confidence: 99%
“…Some neighboring cells were smaller, some bigger and some nearly the same sized. According to Muliyah et al (2018), idioblast can be distinguished by the cell content since idioblast is morphologically similar to neighboring cells. In the present study, idioblast stained red color more intense than neighboring cells, possibly indicating the cell content.…”
Section: Microscopic Evaluation Of Leafmentioning
confidence: 99%